The Aberrant DNA Methylation Profile of Human Induced Pluripotent Stem Cells Is Connected to the Reprogramming Process and Is Normalized During In Vitro Culture - Tesarova, Lenka; Simara, Pavel; Stejskal, Stanislav; Koutna, Irena (PLoS One, 2016)
The potential clinical applications of human induced pluripotent stem cells (hiPSCs) are limited by genetic and epigenetic variations among hiPSC lines and the question of their equivalency with human embryonic stem cells (hESCs). We used MethylScreen technology to determine the DNA methylation profile of pluripotency and differentiation markers in hiPSC lines from different source cell types compared to hESCs and hiPSC source cells. After derivation, hiPSC lines compromised a heterogeneous population characterized by variable levels of aberrant DNA methylation. These aberrations were induced during somatic cell reprogramming and their levels were associated with the type of hiPSC source cells. hiPSC population heterogeneity was reduced during prolonged culture and hiPSCs acquired an hESC-like methylation profile. In contrast, the expression of differentiation marker genes in hiPSC lines remained distinguishable from that in hESCs. Taken together, in vitro culture facilitates hiPSC acquisition of hESC epigenetic characteristics. However, differences remain between both pluripotent stem cell types, which must be considered before their use in downstream applications.
Keywords: buněčná diferenciace; Humans; Cluster Analysis; Induced Pluripotent Stem Cells; lidé; lidské embryonální kmenové buňky; Cells, Cultured; buněčné linie; Gene Expression Regulation, Developmental; indukované pluripotentní kmenové buňky; DNA Methylation; metylace DNA; Cell Line; kultivované buňky; Cell Differentiation; stanovení celkové genové exprese; shluková analýza; Human Embryonic Stem Cells; fibroblasty; vývojová regulace genové exprese; Cellular Reprogramming; Gene Expression Profiling; Fibroblasts; přeprogramování buněk